Mengukur Kualitas Pelayanan Publik di Dinas Kependudukan dan Catatan Sipil Kabupaten Lombok Barat - Rifaid Rifaid; M. Ulfatul Akbar Jafar; M. Taufik Rachman; Johan Natirius (Jurnal Pemerintahan dan Politik Lokal, 2022)
This study aims to determine the quality of public services at the Dukcapil Service of West Lombok Regency. departing from the results of research using qualitative methods. Data collection techniques used interviews, observation and documentation. There are four things to measure the quality of public services at the Dukcapil Service in West Lombok, namely, Tangiabel, reliability, responsiveness, assurance, and empathy. The results show that the quality of public services in the Dukcapil West Lombok meets quality public service standards, with the fulfillment of service facilities according to community expectations and added commitment through regulations in the form of a Decree of the Head of the Population and Civil Registry Office in 2021 related to public service standards within the Dukcapil West Lombok. which regulates service mechanisms and procedures, guarantees time, costs, service culture and the availability of facilities for people with special needs (disabled).